القيم الحجاجية في كتاب الأدب الصغير لابن المقفع - بكوش, تامة, الزهرة أحلام (Univercty of Eloued, 2020)
يهدف هذا البحث إلى الكشف عن القيمة الحجاجية للأليات اللغوية والبلاغية في كتاب يهدف الأدب الصغير لابن المقفع، وقد علمنا على ابراز المقاصد الحجاجية من خلال الآليات اللغوية الموظفة على اختلافها من الروابط وعوامل، وكذلك أساليب التوكيد والتكرار وأفعال الكلام، والآليات البلاغية من استعارات وتشبيه وكنايات وكذلك البديع بمختلف ألوانه والإيجاز والشواهد من حكم وأمثال. وتوصلنا في الأخير إلى أن كتاب الأدب الصغير لابن المقفع يحمل قيمة حجاجية بارزة في إقناع القارئ والتأثير فيه. This research aims to cover the argumentative value of the linguistic and rhetorical mechanisms in the book of al-Adab al-Saghir by Ibn al-Muqaffa, and we have learned to highlight the argumentative intentions through the linguistic mechanisms employed in their various forms of connections and factors, as well as methods of affirmation, repetition, verbs of speech, and rhetorical mechanisms such as metaphors, similes and metaphors, as well as in, brevity evidence from judgment and proverbs. In the end, we concluded that the book Al-Adab Al-Saghir by Ibn AlMuqaffa 'carries an outstanding argumentative value in persuading and influencing the reader.
Keywords: القيمة - الحجاج – القيمة الحجاجية - الآليات اللغوية – الآليات البلاغية.; The value - arguments - the argumentative value - the linguistic mechanisms -the rhetorical mechanisms.